A meta-analysis of customer loyalty in the banking Services - Valipour, Ali; Noraei, Mahmoud; Kavosh, Kamyar (UI Scholars Hub, 2021)
Abstract: This paper presents a systematic framework via a meta-analytical approach to distinguish various dimensions of customer loyalty in the banking industry. Manuscript type: Documentary Research. Research Aims: Presenting a systematic framework of customer loyalty in the banking industry. Design/methodology/approach: The authors conducted searches in various databases and analysed 146 observations in 27 articles. For the quantitative data analysis, the authors used the count of variable repetitions to measure the size and scope of the studied variables. Research Findings: The findings of this meta-analysis demonstrated four dimensions of customer loyalty in the banking sector: behavioral loyalty, attitudinal loyalty, cognitive loyalty and affective loyalty. These four dimensions were derived from 25 variables. Theoretical Contribution/Originality: This research has clarified the dimensions of customer loyalty in the banking sector and presented important results through a meta-analytical review. This meta-analysis contributes to the marketing literature using a set of empirical generalizations, including relationship coefficients and calculated fail-safe numbers. Practitioner/Policy Implication: The results show that according to the four main dimensions of loyalty, managers should care about customer loyalty because it results from the consumer’s banking outcomes. Research limitation/Implications: This meta-analysis reviewed universal relations between literature throughout expanding and improving on current knowledge. It identified ways that research on customer loyalty in the banking sector is lacking and presents suggestions for the elaboration of new studies to allow future researchers to better define their agendas.